2023
DOI: 10.3390/su152316427
|View full text |Cite
|
Sign up to set email alerts
|

The “Modern” Campus: Case Study in (Un)Sustainable Urbanism

Michael W. Mehaffy,
Nikos A. Salingaros,
Alexandros A. Lavdas

Abstract: The design of campuses, like other aspects of contemporary environmental design, must be reassessed in light of the challenge of sustainability. This paper considers the “modern” campus design typology (including business campuses, commercial districts, hospitals, and schools) as a design paradigm for pedestrian public space, with implications for human flourishing and well-being. Its findings point to a serious problem: while the foundational design theories of a century ago have been widely critiqued as an o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 128 publications
1
0
0
Order By: Relevance
“…Carefully designed landscape forms are more easily perceived and understood by observers with abundant knowledge and rich ideas. Similar findings were observed in studies conducted by Michael W. M. et al, which noted that individuals tend to pay more attention to architectural facades and some artificial architectural decorations when appreciating campus scenery [55]. Xu et al found in an experiment comparing the recovery capabilities of Chinese cultural and natural landscapes that cultural landscapes have a similar impact on mental recovery as natural landscapes.…”
Section: The Impact Of Element Combinations On Stress Reliefsupporting
confidence: 82%
“…Carefully designed landscape forms are more easily perceived and understood by observers with abundant knowledge and rich ideas. Similar findings were observed in studies conducted by Michael W. M. et al, which noted that individuals tend to pay more attention to architectural facades and some artificial architectural decorations when appreciating campus scenery [55]. Xu et al found in an experiment comparing the recovery capabilities of Chinese cultural and natural landscapes that cultural landscapes have a similar impact on mental recovery as natural landscapes.…”
Section: The Impact Of Element Combinations On Stress Reliefsupporting
confidence: 82%
“…In conclusion, the related research on campus public spaces and the sense of security has accumulated a substantial body of work, primarily focusing on perspectives such as environmental design and planning [49], psychological factors [50], and technological applications [51]. This has provided a solid research foundation for exploring the evaluation and optimization of a sense of security.…”
Section: Evaluation Of the Literature Reviewmentioning
confidence: 99%